2000
DOI: 10.1074/jbc.m006218200
|View full text |Cite
|
Sign up to set email alerts
|

Low Chloride Stimulation of Prostaglandin E2Release and Cyclooxygenase-2 Expression in a Mouse Macula Densa Cell Line

Abstract: Reducing luminal NaCl concentration in the macula densa region of the nephron stimulates renin secretion, and this response is blocked by a specific inhibitor of cyclooxygenase-2 (COX-2) (Traynor, T. R., Smart, A., Briggs, J. P., and Schnermann, J. (1999) Am. J. Physiol. Renal Physiol. 277, F706 -710). To study whether low NaCl activates COX-2 activity or expression we clonally derived a macula densa cell line (MMDD1 cells) from SV-40 transgenic mice using fluorescence-activated cell sorting of renal tubular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(161 citation statements)
references
References 42 publications
(48 reference statements)
15
143
3
Order By: Relevance
“…However, stimulation of calpain and scramblase are not functionally linked as PGE 2 -induced phosphatidylserine exposure is not inhibited by calpain inhibitors I/II. The latter result is in accordance with a previous study demonstrating that ionomycin-induced 33 In a former study, it has been shown that mechanically stressed adult human red blood cells produce PGE 2 . 34 Furthermore, evidence was presented earlier for PGE 2 induced activation of a nonselective cation channel, 22 for PGE 2 stimulated increase in cytosolic free Ca 2 þ concentration, 23 and PGE 2 -induced release of K þ from erythrocytes, which was blunted by inhibitors of Ca 2 þ -dependent K þ channels.…”
Section: Discussionsupporting
confidence: 82%
“…However, stimulation of calpain and scramblase are not functionally linked as PGE 2 -induced phosphatidylserine exposure is not inhibited by calpain inhibitors I/II. The latter result is in accordance with a previous study demonstrating that ionomycin-induced 33 In a former study, it has been shown that mechanically stressed adult human red blood cells produce PGE 2 . 34 Furthermore, evidence was presented earlier for PGE 2 induced activation of a nonselective cation channel, 22 for PGE 2 stimulated increase in cytosolic free Ca 2 þ concentration, 23 and PGE 2 -induced release of K þ from erythrocytes, which was blunted by inhibitors of Ca 2 þ -dependent K þ channels.…”
Section: Discussionsupporting
confidence: 82%
“…The MD cell line was generated by FACS sorting cells from mice transgenic for the SV40 large T antigen, and has been previously characterized (15). By using specific primers for each renal OR, we found that Olfr 90 is expressed in the MD cell line.…”
Section: Ac3 and Golfmentioning
confidence: 99%
“…Because AC3 and G olf localized to the MD by immunohistochemistry, we also performed PCR on a MD cell line (15) to determine whether any of the renal ORs were expressed in the MD. The MD cell line was generated by FACS sorting cells from mice transgenic for the SV40 large T antigen, and has been previously characterized (15).…”
Section: Ac3 and Golfmentioning
confidence: 99%
“…Could the expression of these two pathways in the juxtaglomerular apparatus (JGA) also reflect the existence of vasodepressor mechanisms that might attenuate afferent arteriolar myogenic reactivity in settings in which distal delivery is impaired? Several investigators have demonstrated that signals reflecting reduced distal delivery, such as reduced osmolality or chloride concentration, trigger the release of NO and PGE 2 from the JGA (121,156,170,173), and direct, microelectrode measurements demonstrate an elevation in distal tubular NO concentration in response to furosemide (95). If severe reductions in distal delivery trigger the combined release of NO and PGE 2 , this would be a powerful vasodilator signal.…”
Section: Interactions Between Myogenic and Tgf Mechanismsmentioning
confidence: 99%